Paredão de cachoeiras : uma nova fitofisionomia(?), caracterização ambiental, método de amostragem da flora e composição florística - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Studies in environments associated with waterfalls are practically nonexistent in Brazil, and deal with favorable places to shelter a peculiar plant diversity due to the horizontal altitude, an adaptation to periodic floods and the presence of different substrates. In the paragraphs of the waterfalls it is important to carry out or raise floristics in conjunction with the variation in altitude and height interrelated with the rocky substrate and water availability. The State of Goiás has a high number of waterfalls and these riparian environments demand research that expands scientific knowledge for subsidiary actions of environmental education and conservation strategies. For example, the present study aimed to determine the composition and floristic structure and the influence of altitudinal gradients on the vegetation of waterfall walls in Quirinópolis, GO. Accepting the different aspects defined in the dissertation networks, this was divided into 4 chapters. In general, constant, despite the waterfall environments studied share similarities with Mata da Galeria, Mata Ciliar, Campo Limpo Humido and Campo Rupestre, none of the phytophysiognomies already addressed in their waterfall subtypes conclusively. So, require a botanical collection to understand the floristic composition. The method for floristic survey on waterfall walls uses vertical abseiling and climbing techniques applied to botanical collection and captures an applied methodology, considering the peculiarities of difficult to access places. He concluded that the bonding technique applied to the collection of botanists results in the effective method for using data from waterfall walls. In this way, an adaptation and / or development of demonstrated collection methods is essential to meet the particularities of each study area. As for the characterization of the physical aspects, the four walls have soil with a sandy textural class and low content of organic matter characterizing Neolithic Litolics. The edaphic parameters present a strong similarity between the walls of the waterfalls. The altitudinal gradient in the study areas varies between 600 and 800m. In the walls of the waterfalls, the forest face is abruptly replaced by the countryside. Among the components of the natural landscape, those maintained in whole or in part contribute positively to the conservation of the environments constituted by the waterfalls. 1,031 specimens were collected. The individuals are distributed in 126 samples of bryophytes, 117 specimens of ferns and lycophytes and 788 specimens of angiosperms. As for angiosperms, specimens of 135 genera belonging to 52 families were registered, the most representative in number of morphospecies: Asteraceae (48), Poaceae (30), Cyperaceae (20), Fabaceae (20) and Melastomataceae (11). The herbaceous-subshrub habit predominates (83.3%) in all the walls of the waterfalls sampled, featuring a predominantly rural appearance with well-defined boundaries with the bush-tree vegetation of the cerrado.
Waterfall wall : a new phytophysiognomy (?), Environmental characterization, flora sampling method and floristic composition
Keywords: Áreas úmidas; Comunidades vegetais ripárias; Conservação flora do Cerrado; Vegetação ripária; Wetlands; Riparian plant communities; Cerrado flora conservation; Riparian vegetation; CIENCIAS BIOLOGICAS